Strategi Peningkatan Kompetensi Pustakawan Di Masa Krisis Dengan Pendekatan Spiritual, Intelektual, dan Emosional - Amalliah Kadir (Jurnal IPI (Ikatan Pustakawan Indonesia), 2022)
The role of librarians is as Human Resources (HR) who work as organizers of library activities by providing services to the community in accordance with the duties of the institutions they are sheltered and their knowledge. Librarians are required to always improve competence and professionalism in carrying out their duties and functions. This is intended so that librarians can compete and collaborate with other information professions, especially to advance the world of librarianship. Competence and professionalism are the most important things for librarians in specialized libraries in maintaining and improving their existence in their work environment. In early 2020 Coronavirus Disease 2019 (Covid-19) has been declared a pandemic that has hit Indonesia. This has an impact on all sectors including the field of education from the level of basic education to higher education, thus affecting the quality of services in the Library. This study aims to explain strategies for increasing the competence of librarians in times of crisis with spiritual, intellectual, and emotional approaches. The research method used is literature research with a qualitative approach to case studies and exploratory research data analysis techniques. The data collection techniques carried out are editing, organizing, and finding. The research instrument is the researcher himself (human instrument) with data sources from primary data and secondary data. The results of the study that increasing the competence of librarians during a crisis: (1) the Covid-19 pandemic affects library services, thus requiring changes to certain rules that are clear in their mechanisms, (2) Rule changes made during a crisis must be reviewed from the readiness of staff and the readiness of supporting devices, (3) The importance of utilizing IT equipment to support library services in times of crisis, (4) innovating services in times of crisis, (5) strategies for increasing the competence of librarians in times of crisis with spiritual, intellectual, and emotional approaches. Librarians will be able to produce innovation and maximum work in all fields they carry out, which can be proven through how much the existing services are accessed by the wider community directly or digitally.